The Effectivness of Five-Finger Hypnosis Theraphy to Decrease on Family’s Anxiety Levels in the Intensive Care Unit - Azizah, Lilik Ma'rifatul; Zainuri, Imam; Akbar, Amar (Kirana Publisher (KNPub), 2023)
Patients in critical or life-threatening conditions who require quick and appropriate help in the emergency room (IGD) with uncertainty about the situation and patient safety, families often experience anxiety. Therapeutic hypnosis five fingers can help mengatatasi anxiety. Five- finger hypnosis therapy is a form of self-hypnosis that can cause a high relaxation effect, so it will reduce tension and anxiety from one's mind. The purpose of this study was to prove the effect of five-finger hypnosis therapy on the level of family anxiety in the emergency department (IGD) RSUD RA Basoeni Mojokerto. The research method used was pre-experimental design with one group pre-test-post-test design. The population of all patients' families in the emergency department (IGD ) RSUD RA Basoeni Mojokerto amounted to 129 . The sampling technique used in this research is Concecutive sampling. so that the sample obtained as many as 17 respondents . The instrument in this study was a questionnaire. Based on the results of the Wilcoxon signed rank test analysis, it was found that the p value = 0.000 and = 0.05 then this shows p < which means this research shows that there is a meaning that there is an effect of five finger hypnosis therapy on the level of family anxiety in the Emergency Installation of RA Basoeni General Hospital Mojokerto . Giving five-finger hypnosis therapy is a form of diverting self-hypnosis situations that can cause a relaxing effect, so that it will reduce anxiety, tension, and stress from one's mind which can have an effect on decreasing anxiety level scores.